2020
DOI: 10.3390/su12187342
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of ASD Classrooms: Specialised Open Classrooms in the Community of Madrid

Abstract: Autism spectrum disorder (ASD) classrooms are specialised spaces within mainstream schools that respond to the educational needs of students with autism spectrum disorder. This research aims to analyse ASD classrooms in the Community of Madrid, their features and internal functioning. The research follows a non-experimental, descriptive and comparative methodology, making a comparison between different classrooms and analysing their impact on the teaching-learning process of students with ASD. The variables re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…However, we have found that, currently, this professional training is neither unified nor shared across university programs, this is, in part, due to the extinction of the former programs of psycho-pedagogy and special needs education and their substitution with a specialization within the degrees in pre-primary and primary education under the Bologna Process [5]. As shown in a recent article about the analysis of autism spectrum disorder (ASD) classrooms, half of teachers do not feel that they have received the correct initial training for starting their professional activity [13].…”
Section: Introductionmentioning
confidence: 99%
“…However, we have found that, currently, this professional training is neither unified nor shared across university programs, this is, in part, due to the extinction of the former programs of psycho-pedagogy and special needs education and their substitution with a specialization within the degrees in pre-primary and primary education under the Bologna Process [5]. As shown in a recent article about the analysis of autism spectrum disorder (ASD) classrooms, half of teachers do not feel that they have received the correct initial training for starting their professional activity [13].…”
Section: Introductionmentioning
confidence: 99%